Case Study: Future Home Design Project for Developing Pro-Environmental Attitudes - Eko Yuliyanto (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
The results of the learning evaluation indicate that many students do not apply to pro-environmental attitudes. This case study research investigated the potential of making future home designs to develop a pro-environmental attitude. The study was conducted in two stages and involved thirty-five students. In the first stage, the students discussed plants, water, electricity, and garbage at home. The results of the discussion were formulated to be future home designs. In the second stage, the students designed future homes. The results show that the students can implement their ideas into 2-dimensional (2D). The results indicate that most of the students can implement their ideas as much as 86%. The students enthusiastically participated in the learning process. The results show that all students have plants, 11% use Light Emitting Diode (LED), 6% use solar lighting, 71% use proper water sanitation, 54% apply waste management, and 81% have bio pores. It can be concluded that future home design project has the potential to develop a pro-environment attitude.